2022
DOI: 10.3390/app12073325
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Properties of Calcareous Sands from Urban Areas of Abu Dhabi

Abstract: Abu Dhabi (ABD) has recently developed its national building code that mandates dynamic analysis of large structures to seismic loadings. Large strain dynamic properties such as shear modulus (G) and damping ratio (D) of local undisturbed calcareous sands are not available. Designers are compelled to choose degradation models from studies on calcareous sands of other regions that are usually reconstituted. This research presents for the first time large strain dynamic properties of calcareous sands of urban AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Low-strain Vs is required to classify sites for seismic analysis, and corresponding amplification factors for ground accelerations are determined. Dynamic properties are typically obtained by conducting field and laboratory tests (Khan et al [ 1 ]; Khan et al [ 2 ]; Khalil et al [ 3 ]; Irfan et al [ 4 ]). These tests have various limitations and testing biases related to boundary conditions, assumptions, attainable strains and frequencies (e.g., Khan et al [ 1 ]; Clayton et al [ 5 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-strain Vs is required to classify sites for seismic analysis, and corresponding amplification factors for ground accelerations are determined. Dynamic properties are typically obtained by conducting field and laboratory tests (Khan et al [ 1 ]; Khan et al [ 2 ]; Khalil et al [ 3 ]; Irfan et al [ 4 ]). These tests have various limitations and testing biases related to boundary conditions, assumptions, attainable strains and frequencies (e.g., Khan et al [ 1 ]; Clayton et al [ 5 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of the studies are contrary to expectations, which caused more interest; the main reasons for the unexpected results are still not fully understood, but should be in order to better design future experiments. Typically, Vs as a function of shear strains is measured with a combination of resonant column (RC) and cyclic triaxial (CT) devices which require additional resources (e.g., Khan et al [ 1 ], Khalil et al [ 3 ]). Bender elements (BE) have been extensively used to determine low-strain Vs (Dyvik and Madshus [ 10 ], Shirley and Hampton [ 11 ], Viggiani and Atkinson [ 12 ], Kuwano and Jardine [ 13 ], Gu et al [ 14 ], Khalil et al [ 3 ]; Irfan et al [ 4 ]).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the small-strain shear modulus and damping ratio of calcareous sand under isotropic or anisotropic stress consolidated state have been studied [22][23][24][25]. The effects of confining stress, pore ratio, relative density, grading and particle size, and particle breakage on the dynamic properties are discussed [21,[25][26][27][28][29]. Morsy et al [26] found the effect of void ratio on shear modulus was more pronounced at low void ratios and maximum shear modulus increased as the void ratio decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Hassanlourad et al [28] studied the shear behavior of calcareous sand through drained and undrained triaxial tests and reported the effect of particle breakage on specimen response. Khalil et al [29] performed a series of bender element and cyclic triaxial tests to study the low-strain and large-strain characterization of calcareous sand and terrigenous sand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation